Development of E-Learning Materials Assisted by Augmented Reality on Human Digestive System Material to Improve Elementary School Students' Learning Outcomes - Muhammad Wahyu Agung Risqiyono; Novi Setyasto (Postgraduate, University of Mataram, 2025)
This study aims to develop, test the feasibility, effectiveness, and practicality of Augmented Reality (AR)-assisted e-learning materials to improve student learning outcomes. This study is a Development Research (R&D) using the Borg and Gall model. This study involved 42 fifth grade students of Kedungmundu State Elementary School (SDN) in the 2024/2025 academic year, with a small-scale trial on 15 VA class students and a large-scale trial on 27 VB class students. Data collection techniques used test techniques (pretest - posttest) and non-test in the form of interview results, questionnaires, observations, score lists, and documentation. The results of validation by material, language, and media experts which showed that AR-assisted e-learning materials were declared